Money on the Mind: Investigating the Link between Attitude toward Money and Online Gambling Intention - Maria; Tuti Setyorini; Indawati Jauhar Nino (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2025)
This paper considers the relationship between attitudes toward money and online gambling intention among young adults in Indonesia and whether financial literacy helps explain this relationship. Drawing on survey evidence from 211 respondents aged between 18 and 35, the findings suggest that particular orientations toward money are associated with different levels of vulnerability to online gambling. Specifically, the Power-Prestige dimension is positively related to online gambling intention, suggesting that individuals who attach status and symbolic value to money may be more inclined to engage in such behaviour. By contrast, Distrust is negatively associated with online gambling intention, suggesting a more cautious orientation toward financial decisions. The analysis further shows that financial literacy plays an important mediating role. In the relationship between Power-Prestige and online gambling intention, financial literacy appears to weaken the tendency toward gambling participation. However, in the relationship between Distrust and online gambling intention, financial literacy operates in the opposite direction. Taken together, these findings indicate that financial literacy is not merely a technical capacity but may function as a cognitive mechanism through which individuals interpret financial risk, opportunity, and self-control. The study contributes to the literature on financial behaviour by showing how psychological attitudes toward money shape risky financial intentions, and it offers practical implications for financial education programmes and interventions aimed at young adults.